Thermodynamic and economic analysis, optimization of SOFC/GT/SCO2/ORC hybrid power systems for methanol reforming-powered ships with carbon capture - Shouguang Yao; Xuan Yan; Minjie Xia; Chuang Wang; Shaofan Wang (Case Studies in Thermal Engineering)
To realize the efficient use of energy and reduction of emissions of the power system of ocean-going vessels, a 25,000-ton chemical ship is used as the subject of this study. A hybrid power system containing carbon capture based on methanol external reforming of solid oxide fuel cell coupled with gas turbine is proposed, further to achieve efficient energy use and reduce carbon emissions, the power system combines a supercritical CO2 cycle with an organic Rankine cycle in order to optimize the utilization of waste heat, and chemical absorption method for carbon capture. The proposed novel power system is analyzed for the impact of important factors of each system on performance of the system, and thermodynamic and economic analyses and evaluations are carried out. Ultimately, a genetic algorithm-based approach was employed to optimize the system's performance through multi-objective optimization, aiming for the best possible outcome. The optimized outcome shows that the system's net output power has reached 4743.81 kW, which fully satisfies the power requirements of the target vessel. Additionally, it achieves a carbon capture rate of 81.52 %, an energy efficiency of 60.56 %, and the cost of electricity production is 0.08727 $/kWh. The system realizes excellent thermodynamic performance and economy.